1973
DOI: 10.1071/bi9730605
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin Polymorphisms in the Echidna, Tachyglossus Aculeatus

Abstract: Echidnas and platypuses possess two haemoglobins, HbI and HbII. HbI is in the higher concentration. Genetic variation has been found in the electrophoretic mobility of both HbI and HbII in the echidna.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A hybrid zone exists, extending outwards from central coastal New South Wales, in which echidnas have either Hb-IA or Hb-IB or are heterozygous for Hb-IA and Hb-IB. Echidnas on mainland Australia have Hb-nA, but polymorphism of this haemoglobin occurs in Tasmania (Cooper et al 1973). Haemoglobin Hb-nA has a markedly higher oxygen affinity than Hb-IA and Hb-IB; this higher affinity is related to a difference in the DPG interaction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hybrid zone exists, extending outwards from central coastal New South Wales, in which echidnas have either Hb-IA or Hb-IB or are heterozygous for Hb-IA and Hb-IB. Echidnas on mainland Australia have Hb-nA, but polymorphism of this haemoglobin occurs in Tasmania (Cooper et al 1973). Haemoglobin Hb-nA has a markedly higher oxygen affinity than Hb-IA and Hb-IB; this higher affinity is related to a difference in the DPG interaction.…”
Section: Methodsmentioning
confidence: 99%
“…Starch-gel electrophoresis of the echidna haemolysates was carried out at pH 8·6 as described by Hosken (1978). When the resulting bands were compared with those described by Cooper et al (1973), the blood of one animal contained Hb-IA and Hb-IIA, the second animal had Hb-IB and Hb-IIA, and the third had Hb-IA, Hb-IB and Hb-IIA. Cells were collected from the blood by centrifugation, washed in 0·9% (w/v) saline and the haemolysate prepared as described by Hosken (1978).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discontinuous buffer system of Poulik (1957) at pH 8·6 was used. The echidna haemoglobin used was a mixture of Hb-IB and Hb-IIA (Cooper et al 1973).…”
Section: Electrophoresismentioning
confidence: 99%
“…In Parts I and II of this series (Whittaker et al 1972(Whittaker et al , 1973) the fractionation of the haemoglobins and of the globin chains from the south-eastern Australian echidna Tachyglossus aculeatus aculeatus (Cooper et al 1973) was reported, together with the amino acid sequences of the a-and f3-g1obin chains of the major haemoglobin component, Hb-IB.…”
Section: Introductionmentioning
confidence: 99%